Can community health workers increase coverage of reproductive health services?. Issue 10 (7th November 2011) - Viswanathan, Kavitha; Hansen, Peter M; Rahman, M Hafizur; Steinhardt, Laura; Edward, Anbrasi; Arwal, Said Habib; Peters, David H; Burnham, Gilbert
Abstract : Background: Health services were severely affected during the many years of instability and conflict in Afghanistan. In recent years, substantial increases in the coverage of reproductive health services have been achieved, yet absolute levels of coverage remain very low, especially in rural areas. One strategy for increasing use of reproductive health services is deploying community health workers (CHWs) to promote the use of services within the community and at health facilities. Methods: Using a multilevel model employing data from a cross-sectional survey of 8320 households in 29 provinces of Afghanistan conducted in 2006, this study determines whether presence of a CHW in the community leads to an increase in use of modern contraceptives, skilled antenatal care and skilled birth attendance. This study further examines whether the effect varies by the sex of the CHW. Results: Results show that presence of a female CHW in the community is associated with higher use of modern contraception, antenatal care services and skilled birth attendants but presence of a male CHW is not. Community-level random effects were also significant. Conclusions: This study provides evidence that indicates that CHWs can contribute to increased use of reproductive health services and that context and CHW sex are important factors that need to be addressed in programme design.